2023
DOI: 10.1002/mc.23606
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 loss promotes colorectal cancer cell metastasis through regulating TNIK expression and actin cytoskeleton remodeling

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors. Approximately 5%–6% of CRC cases are associated with hereditary CRC syndromes, including the Peutz–Jeghers syndrome (PJS). Liver kinase B1 (LKB1), also known as STK11, is the major gene responsible for PJS. LKB1 heterozygotic deficiency is involved in intestinal polyps in mice, while the mechanism of LKB1 in CRC remains elusive. In this study, we generated LKB1 knockout (KO) CRC cell lines by using CRISPR‐Cas9. LKB1 KO promoted CRC cell motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…For instance, leucine zipper tumor suppressor family member 3 (LZTS3) regulated CRC cell proliferation, migration, and actin cytoskeleton, which inhibited the progression of CRC [22]. A study by Guanghui Hu et al showed that the loss of liver kinase B1 (LKB1) facilitated tumor cell metastasis in CRC via the upregulation of TRAF2 and NCK-interacting protein kinase (TNIK) and subsequently induced cytoskeleton remodeling [23]. In addition, phospholipase C Beta 1 (PLCB1) depletion resulted in a decrease in gastric cancer cell migration, and invasion by modulating actin cytoskeletal remodeling and EMT [24].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, leucine zipper tumor suppressor family member 3 (LZTS3) regulated CRC cell proliferation, migration, and actin cytoskeleton, which inhibited the progression of CRC [22]. A study by Guanghui Hu et al showed that the loss of liver kinase B1 (LKB1) facilitated tumor cell metastasis in CRC via the upregulation of TRAF2 and NCK-interacting protein kinase (TNIK) and subsequently induced cytoskeleton remodeling [23]. In addition, phospholipase C Beta 1 (PLCB1) depletion resulted in a decrease in gastric cancer cell migration, and invasion by modulating actin cytoskeletal remodeling and EMT [24].…”
Section: Discussionmentioning
confidence: 99%